National Interest and National Identity Affect The Behaviour Of Foreign Policy - Syaravina Lubis (Mahadi: Indonesia Journal of Law, 2023)
There was a time when national identity influenced foreign policy, as in China, which has its Buddhist impermanence derived from its cultural identity. It has the identity of, and is derived from Japan's experience of the war in its own country. National interests on foreign policy actions are stronger than that of national identity. It targets countries without strong national identity clout, such as Western European countries such as Germany, and other countries such as the United States and Indonesia. The existence of strong national identities therefore only reinforces the influence of national interests influencing foreign policy, as has happened in China and Japan. Indonesia has Pancasila as its national identity. It has influenced its foreign policy by recognizing external threats. Moreover, Pancasila's national identity influences Indonesia's interior rather than its foreign policy. During the New Order era, China was known to be a communist threat to Indonesia, and Indonesia cut ties with China. In Europe and the United States, where societies have become multicultural societies, national interests influence foreign policy more than national identity. We should have more influence on our foreign policy to unite our national interests and multicultural societies.